Worldwide Esophageal Cancer Collaboration: pathologic staging data. Issue 7 (1st October 2016) - Rice, T. W.; Chen, L.-Q.; Hofstetter, W. L.; Smithers, B.M.; Rusch, V. W.; Wijnhoven, B. P. L.; Chen, K. L.; Davies, A. R.; D'Journo, X. B.; Kesler, K. A.; Luketich, J. D.; Ferguson, M. K.; et al.
Summary: We report data—simple descriptions of patient characteristics, cancer categories, and non–risk-adjusted survival—for patients with pathologically staged cancer of the esophagus and esophagogastric junction after resection or ablation with no preoperative therapy from the Worldwide Esophageal Cancer Collaboration (WECC). Thirty-three institutions from six continents submitted de-identified data using standard definitions: demographics, comorbidities, clinical cancer categories, and all-cause mortality from first management decision. Of 13, 300 patients, 5, 631 had squamous cell carcinoma, 7, 558 adenocarcinoma, 85 adenosquamous carcinoma, and 26 undifferentiated carcinoma. Patients were older (62 years) men (80%) with normal body mass index (51%), little weight loss (1.8 kg), 0–2 ECOG performance status (83%), and a history of smoking (70%). Cancers were pT1 (24%), pT2 (15%), pT3 (50%), pN0 (52%), pM0 (93%), and pG2-G3 (78%); most involved distal esophagus (71%). Non–risk-adjusted survival for both squamous cell carcinoma and adenocarcinoma was monotonic and distinctive across pTNM. Survival was more distinctive for adenocarcinoma than squamous cell carcinoma when pT was ordered by pN. Survival for pTis-1 adenocarcinoma was better than for squamous cell carcinoma, although monotonic and distinctive for both. WECC pathologic staging data is improved over that of the 7th edition, with more patients studied and patient and cancer variables collected. These data will be the basis for the 8th edition cancer staging manuals following risk adjustment for patient, cancer, and treatment characteristics, and should direct 9th edition data collection. However, the role of pure pathologic staging as the principal point of reference for esophageal cancer staging is waning.